2022
DOI: 10.3390/ijerph191710792
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Mothers’ Adherence to Home Exercise Programs Designed for Their Children with Cerebral Palsy

Abstract: Cerebral palsy is a common motor disorder that results in long-term impairment. The purpose of this study was to find out what factors influence Saudi mothers’ compliance with their Children with Cerebral Palsy (C-CP) Home Exercise Program (HEP). A self-administered online questionnaire was used to perform this qualitative research study on a group of 113 mothers who had children with CP. The study included mothers with children from birth to 12 years old who had received a HEP prescription from a physiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The current review also noted that factors such as social support and self-efficacy were sometimes assessed using a single item derived from related validated scales, which may not effectively capture the target concepts [ 32 , 35 , 37 ]. Other research efforts have tried to mitigate these issues by developing new measures based on existing scales or theories in the scientific literature [ 22 , 35 , 37 ] or by pre-testing and piloting the scales.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current review also noted that factors such as social support and self-efficacy were sometimes assessed using a single item derived from related validated scales, which may not effectively capture the target concepts [ 32 , 35 , 37 ]. Other research efforts have tried to mitigate these issues by developing new measures based on existing scales or theories in the scientific literature [ 22 , 35 , 37 ] or by pre-testing and piloting the scales.…”
Section: Resultsmentioning
confidence: 99%
“…These studies suggested that parental education helps parents feel less anxious about injuring or causing harm to their children. Further, the association between the caregiver’s age and HEPA was inconsistent [ 22 , 34 , 35 , 39 ]. Only one study out of four indicated significant positive associations [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] The current review found that factors such as social support and self-e cacy were also assessed by a single item derived from their related validated scales that may not effectively assess target concepts. [33,35] Other research attempted to address these concerns by developing new measures based on existing scales or theories in the scienti c literature [20,33,35] or by pretesting and piloting the scales.…”
Section: Quality Assessment Included Articlesmentioning
confidence: 99%
“…[33,35] Further, parents who were motivated by the therapist advised to insert exercises into daily routines, assessed their skills, or asked about adherence at home by their therapists were more likely to comply with home exercises. [20,33,35,38,40,42] Yet, some authors [43] have highlighted the risk that this follow-up may lead to stress and feelings of guilt in parents. Similarly, Lillo-Navarro and his colleagues [35] suggested that healthcare providers must be aware of this circumstance to be perceived as a source of assistance rather than a judgemental bystander.…”
Section: Physiotherapist's Supportmentioning
confidence: 99%